2014
DOI: 10.1038/bjc.2014.630
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of complications in gynaecological oncological surgery: a prospective multicentre study (UKGOSOC—UK gynaecological oncology surgical outcomes and complications)

Abstract: Background:There are limited data on surgical outcomes in gynaecological oncology. We report on predictors of complications in a multicentre prospective study.Methods:Data on surgical procedures and resulting complications were contemporaneously recorded on consented patients in 10 participating UK gynaecological cancer centres. Patients were sent follow-up letters to capture any further complications. Post-operative (Post-op) complications were graded (I–V) in increasing severity using the Clavien-Dindo syste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
42
0
7

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 51 publications
(53 citation statements)
references
References 27 publications
(44 reference statements)
4
42
0
7
Order By: Relevance
“…It is hardly surprising that patients treated with ‘ultra‐radical’ surgery experience higher rates of major complications than patients managed with standard surgery . Although surgical complexity has long been associated with postoperative morbidity, our study is the first to demonstrate that standard and ‘ultra‐radical’ surgery of similar surgical complexities have similar major complication rates, suggesting that the actual number of procedures performed is a more important driver of postoperative morbidity than the procedure types themselves.…”
Section: Discussionmentioning
confidence: 59%
“…It is hardly surprising that patients treated with ‘ultra‐radical’ surgery experience higher rates of major complications than patients managed with standard surgery . Although surgical complexity has long been associated with postoperative morbidity, our study is the first to demonstrate that standard and ‘ultra‐radical’ surgery of similar surgical complexities have similar major complication rates, suggesting that the actual number of procedures performed is a more important driver of postoperative morbidity than the procedure types themselves.…”
Section: Discussionmentioning
confidence: 59%
“…Iyer and colleagues and Zighelboim and colleagues found age to be a significant predictor of postoperative complications but it is relevant to point out here that they had included only gynecological oncology surgery patients while this study included all women undergoing laparotomy. 6,7 BMI was also not found to be associated with postoperative complications. Previous studies had found that unintentional weight loss, which is a marker of frailty, and morbid obesity (BMI ≥40 kg/m 2 ) are associated with increased major postoperative complications.…”
Section: Discussionmentioning
confidence: 73%
“…This is consistent with the findings of aforementioned studies. 4,6,7 Zighelboim et al recorded comorbidities in the same way as was done in the study (described in ‗Materials and methods') and found multiple comorbidities to be significantly associated (p = <0.00001) with significant postoperative complications. 7 As seen from the results, SAS was found to be significantly associated with postoperative complications.…”
Section: Discussionmentioning
confidence: 99%
“…Surgical data on a national level has been collected in specialties such as cardiothoracic and orthopaedic surgery and certain cancers such as lung, colorectal and head and neck; there is a paucity of such data in gynaecological oncology (GO). To address this, the United Kingdom Gynaecological Oncology Surgical Outcomes and Complications (UKGOSOC) study was undertaken to prospectively capture data on surgery with a view to setting benchmarking standards. In this cohort, the overall intraoperative (IntraOp) complication rate (CR) was 4.7% and the postoperative (PostOp) CR was 25.7% .…”
Section: Introductionmentioning
confidence: 99%
“…To address this, the United Kingdom Gynaecological Oncology Surgical Outcomes and Complications (UKGOSOC) study was undertaken to prospectively capture data on surgery with a view to setting benchmarking standards. In this cohort, the overall intraoperative (IntraOp) complication rate (CR) was 4.7% and the postoperative (PostOp) CR was 25.7% . However, use of observed CRs for centre‐level comparisons does not take into account patient co‐morbidity, underlying disease or surgical complexity, all of which can impact on the risk of a complication .…”
Section: Introductionmentioning
confidence: 99%